Verification of Reliability and Validity of a Malaysian Version of Rathus Assertiveness Schedule as Drug Prevention Scale - Ahmad Jazimin Jusoh; Muh Khairul Wajedi Imami; Ciptro Handrianto; Ahmad Nazir Mohd Isa; Siti Zobidah Omar; Azizi Abdullah; Suzaily Wahab (Islamic Guidance and Counseling Journal, 2023)
The aim of this research was to verify the Malaysian version of Rathus assertiveness as a drug prevention scale in secondary students. The current research articipants were 211 secondary students in Johor, Selangor, and Kuala Lumpur, Malaysia. An exploratory factor analysis with principal axis factoring and varimax rotation was performed for the initial analysis. After the eigenvalue emerged, the data was suppressed to .30 to display the factor loading. The value of commonalities and factor loading was considered to frame and locate the items in the scale structure. Furthermore, the reliability of the scale was tested through Cronbach's alpha. The result showed that nine factors emerged, explaining 58.721% of the variance. Four of the 30 items were eliminated from the analysis because they had commonalities below the threshold. The structure of the scale was as follows: seven items in the first factor, four items in the second factor, four items in the third factor, two items in the fourth factor, two items in the fifth factor, one item in the sixth factor, two items in the seventh factor, two items in the eight factors, and one item in the ninth factor. Furthermore, the reliability of the scale was .748. Meaning that the scale was internally consistent in measuring the secondary student`s assertiveness in drug education.